The Evaluation of Driver Behaviors and Skills Relation with Consumption of Alcohol, Drug Abuse and Medicine in Professional Drivers - Aktaş, Alev; Döğer, Rukiye; Akgür, Serap Annette (The Bulletin of Legal Medicine, 2019)
Introduction: Driver behavior and skills are among the main factors that constitute the risk of accidents in traffic. Driving behavior under the influence of alcohol and drug abuse is an important traffic problem that causes deaths, pecuniary damage and injuries. The aim of the study was to investigate the frequency of alcohol, drug abuse and medicine use in professional drivers and to evaluate the relationship between these substances and driver behavior and skills.Methods: The study was performed with 90 professional drivers working in 4 different town of İzmir. questionnaire form, Fagerström Test for Nicotine Dependence (FTND), CAGE Alcohol Screening Test, Driver Behavior Scale (DBS) and Driving Skills Scale (DSS) were applied to drivers. The data were analyzed statistically with SPSS 18.0 (p
Keywords: Alcohol; Drug Abuse; Driver Behaviours; Driver Skills